PENINGKATAN KECERDASAN KINESTETIK MELALUI KEGIATAN GERAK DAN LAGU (Penelitian Tindakan di Kelompok B TK Pertiwi No.1 Uloe, Kecamatan Dua Boccoe, Kabupaten Bone, Sulawesi Selatan, Tahun 2016) - Ngewa, Herviana Muarifah (EDUCHILD (Journal of Early Childhood Education), 2020)
The purpose of this research to described the process and lessons through the activities of music and movement that would improve bodily kinesthetic intelligence children in group B Kindergarden of Pertiwi No.1 Uloe, academic year 2015/2016. The subject of this research totaled 15 childrens. A method of this research is Action Research of referring to a model research the act of class by Kemmis and MC. Taggart which includes four namely planning stage, action, observation, and reflection. This research consisting of 2 cycles, in the first cycle consists of eight meetings and in the second cycle consists of six sessions. Technique analysis the data used in this research is data analysis qualitative and quantitative. Qualitative data available for analysis by means of analyzed data from the resultsof the field notes, the note interview, and a report on documentation during the survey by steps the reduction of the data, display data, and verification of data. Analysis quantitative data with statistics description that compares the results obtained from pre cycle, first cycle, and second cycle. The result of this research showed an increased kinesthetic intelligence of children through activities music and movement, the average score demonstrable kinesthetic intelligence pre cycle is 23,00, Afterward subjected to increase the first cycle is 31,06 and the socend cycle is 37,80.Keywords: Kinesthetic Intelligence, Music and Movement, Action Research